The Students' Interest in Online Learning in Higher Education During the Covid-19 Pandemic - Dafid Slamet Setiana; Betty Kusumaningrum; Riawan Yudi Purwoko (Edumatika : Jurnal Riset Pendidikan Matematika, 2021)
The Covid-19 pandemic in various countries has had an impact on changes in the education system. The implementation of learning has changed from classroom to online learning. The implementation of online learning certainly affects the learning interest of students. This study was conducted to determine student interest in learning during the Covid-19 pandemic. The subjects in this study were students of the Mathematics Education Study Program at a private university in Yogyakarta as many as 72 students who were selected using the simple random sampling method. The data in this study were collected through Google Form questionnaire. The questionnaire contains 15 items of multiple choice and each item contains “why” question to obtain in-depth data about the answers given by respondents. The data of questionnaire analyzed descriptive qualitatively. The results indicated that students' interest in online learning needed to be insreased. It can be seen from students’ responses to the questionnaire that only 15.3% of students gave a positive response to online learning and 32% to online exams. In general, students prefer classroom learning compared to online learning in terms of student attendance, interaction of lecturer-students, and technical in learning. Online learning tends to reduce student interest in attending lectures. Limitations of internet access, lecturer delivery methods and the amount of workloads are factors causing the decline in student interest. By knowing students' interest in learning and the factors that cause low students’ interest in learning, lecturers can improve the quality of learning to increase student interest in online learning.